2018
DOI: 10.1111/jonm.12693
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of nursing workloads and contributing factors, and their impact on implicit care rationing: A Queensland, Australia study

Abstract: Adequate staffing should be based on patient acuity and the skill-mix required for safe care. Managers should be more assertive about adequate clinical workloads, involve staff in decision-making, and adopt a systematic planning approach. Failure to do so results in implicit care rationing impacting on patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 34 publications
3
60
0
8
Order By: Relevance
“…In work undertaken by Hegney et al. (2018), nurses identified lack of support from managers when they reported their concern at not being able to complete care as a result of reduced budgets and lower staffing levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In work undertaken by Hegney et al. (2018), nurses identified lack of support from managers when they reported their concern at not being able to complete care as a result of reduced budgets and lower staffing levels.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this view, Hegney et al. (2018) found that managers felt vulnerable due to conflicting loyalties between meeting organisational requirements and the need to support staff. As Bill said, budgets are the main focus, which unavoidably takes the focus away from actual ‘care’ and orientates it towards ‘efficiency’ .…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed so far demonstrated that nursing care rationing is a serious issue, present in Western European states, 2 4 5 8 9 the USA 10 11 24 27 and Australia. 12 All these countries are highly developed and have incomparably higher healthcare spending than Poland, 39 possibly suggesting that problems with resource allocation or staff shortages may be less severe there than in Poland. Therefore, the development of a Polish version of a questionnaire measuring the PIRNCA was warranted in order to investigate this issue in Polish settings.…”
Section: Discussionmentioning
confidence: 99%
“…required by a patient, to an extent depending on the patient's condition as determined in the Nursing Diagnosis Process. 1 Sadly, multiple studies on nursing conducted in recent years [2][3][4][5][6][7][8][9][10][11][12] demonstrated the occurrence of the phenomenon of the non-performance or incomplete or delayed performance of tasks involved in providing holistic care for a hospitalised patient.…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to working in specialty units requiring direct patient care and involving fewer patients than in wards and outpatient units. These data must be interpreted with caution because staffing levels and skill‐mix result in implicit care rationing (Hegney et al, ). The current study could not reveal any significant relationship between QNWL and other work characteristics, such as working overtime, method of rotating shifts, compensation for rotating shifts, being certified, current position and leadership position.…”
Section: Discussionmentioning
confidence: 99%